2022
DOI: 10.1590/fst.91721
|View full text |Cite
|
Sign up to set email alerts
|

The lipid source can modify saturated and unsaturated fatty acids profile of meat of lambs

Abstract: We hypothesize that lambs fed diets with different lipids sources from oilseeds would similar performance but fatty acids profile of meat superior to those fed with conventional diets. We evaluated the effects of inclusion of oilseeds on the ingestive behaviour, performance, carcass trait and meat quality in feedlot lambs. Three isonitrogenous (18.31% crude protein) diets were evaluated, where one diet was the standard (control), and the others two diets contained soybean and cottonseed. Fifteen Texel lambs, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
(38 reference statements)
0
5
0
Order By: Relevance
“…Wanderley et al (2022) found that oilseeds can alter the fatty acid (FA) profile in the milk of Girolando dairy cows and concluded that whole soybean provides greater milk and FA yields. In the same way, Rodrigues et al (2022) found that lambs treated with whole soybean have greater amounts of FA, mostly UFA, in their meat. They cited a decrease in cholesterol levels in meat; thus, lambs fed soybean, producing FA, produced enriched meat that benefited human health.…”
Section: Introductionmentioning
confidence: 59%
See 3 more Smart Citations
“…Wanderley et al (2022) found that oilseeds can alter the fatty acid (FA) profile in the milk of Girolando dairy cows and concluded that whole soybean provides greater milk and FA yields. In the same way, Rodrigues et al (2022) found that lambs treated with whole soybean have greater amounts of FA, mostly UFA, in their meat. They cited a decrease in cholesterol levels in meat; thus, lambs fed soybean, producing FA, produced enriched meat that benefited human health.…”
Section: Introductionmentioning
confidence: 59%
“…Despite the fact that the lipid content in the diets with oilseeds inclusion did not exceed 70 g/kg, which is a limit established for cattle, so that there are no adverse effects on intake (NASEM, 2016;Kozloski, 2011), there was a reduction on DMI in all oilseed diets. Nevertheless, lipids are advantageous in diets due to their high energy value, which should be used without harmful effects of FA on rumen fermentation (Ítavo et al, 2005) with possible modification of FA in meat (Ítavo et al, 2021;Miyaki et al, 2022;Rodrigues et al, 2022) and in milk (Wanderley et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The lipids are compounds of vital importance for human nutrition, because although they provide energy for the biological processes in the human body, the lipids contain essential fatty acids or liposoluble vitamins that are only obtained in diet. Moreover, the lipids are responsible for many desirable characteristics of meat and meat products (Adilah & Hanani, 2016;Lima et al, 2022), because they influence the flavor and contribute to the improvement of tenderness and succulence of meats (Ahmed et al, 2017;Domínguez et al, 2018;Rodrigues et al, 2022). The types of fatty acids (FA) in food products can influence both stability during storage and nutritional characteristics, being classified as saturated fatty acids (SFA), monounsaturated fatty acids (MUFA) and polyunsaturated fatty acids (PUFA) (Lucarini et al, 2018).…”
Section: Introductionmentioning
confidence: 99%